On the Effects of Distance Functions to Improve Content-based Image Retrieval - Bugatti, Pedro H.; Traina, Agma J. M. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2009)
The retrieval of images by visual content relies on a feature extractor to provide the most meaningful intrinsic characteristics (features) from the data, and a distance function to quantify the similarity between them. A challenge in this field supporting content-based image retrieval (CBIR) to answer similarity queries is how to best integrate these two key aspects. There are plenty of researching on algorithms for feature extraction of images. However, little attention have been paid to the importance of the use of a well-suited distance function associated to a feature extractor. This Master Dissertation was conceived to fill in this gap. It was also proposed a new technique to perform feature selection over the feature vectors, in order to improve the precision when answering similarity queries. This work also showed that the proper use of a distance function effectively improves the similarity query results. Therefore, it opens new ways to enhance the acceptance of CBIR systems.